PELATIHAN BUDIDAYA RUMPUT LAUT BERKELANJUTAN SISTEM KARAMBA KEPADA PEMBUDIDAYA DAN PENYULUH PERIKANAN - Mulyono, Mugi; Ilham, Ilham; Suharyadi, Suharyadi; Marlina, Erni; Samsuharapan, Sri Budiani; Damanik, Lina Aftiani (Universitas Mataram, 2024)
This training is to increase knowledge and skills in seaweed farming activities. Training is carried out with theory in the classroom and hands-on practice in the field. The training phase in class is based on theory and discussion of problems that occur in the cultivation business. At the field practice stage a performance is carried out so that farmers are able to do and apply between theory and practice. The results of the training can be directly evaluated through training in the practice of planting seaweed to harvest. In general, at the three experimental sites, kreteria growth of seaweed. The karamba system method can be a problem in handling the problem of pests and seaweed damage, this is evidenced from 3 test groups of general problems growing and developing.